Information Governance and Transparency Information: Two Sides of the Same Coin? - Sari, Indah Novita; Mulya, Lillyana; Darajat, Irfan Rizky (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2025)
Background: Information governance plays a central role in ensuring transparency, accountability, and compliance in public institutions. In the context of public administration, particularly in Indonesia, the implementation of information governance remains inconsistent, leading to issues such as information disputes and limited access to public data. The Freedom of Information (FOI) Act was established to promote openness; however, its success depends significantly on the maturity level of information governance in public institutions.Objective: This study aims to analyze the maturity level of information governance in public institutions within the Yogyakarta Special Region and to explore the relationship between information governance and the implementation of the Freedom of Information (FOI) Act. The assessment framework is based on the maturity model developed by the Association of Records Managers and Administrators (ARMA).Methods: A mixed-method approach was employed, combining quantitative and qualitative data. Data were collected through surveys, interviews, and observations involving key informants and respondents, including heads of administrative units, information managers, and records managers. The study was conducted in eight government institutions in the Yogyakarta Special Region.Results: The maturity levels of information governance across the eight institutions vary significantly. They range from sub-standard to in development, essential, and transformational. None of the institutions achieved a fully transformational level. Only the Department of Agriculture attained levels 3 and 4 (essential and transformational) across all eight indicators: accountability, transparency, integrity, protection, compliance, availability, retention, and disposition. Most other institutions remain below the essential standard, especially in accountability and transparency, which are critical components for effective information governance. Furthermore, the study finds a strong interconnection between information governance and freedom of information: effective governance enhances FOI implementation, while the FOI Act positively influences governance practices.Conclusion: The maturity of information governance in public institutions in Yogyakarta remains uneven, with most institutions yet to meet essential standards. Strengthening accountability and transparency should be prioritized. The study concludes that information governance and freedom of information are inherently linked—improving one supports the success of the other. Enhancing information governance is thus essential for realizing the full potential of FOI implementation in public sector institutions.